IMF Staff papers : Volume 33 No. 4. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1986)
This paper outlines potential strengths and weaknesses of various versions of the target zone approach and confronts operational outlines potential strengths and weaknesses of various versions of the target zone approach but also confronts operational. Target zones differ from a pure system of clean floating in that the authorities are permitted (and indeed are likely) to intervene in the exchange market, and, more generally, are encouraged to take a view on the desirable level of the exchange rate. The hard version of target zones shares some of the attributes of the existing European Monetary System (EMS). Unlike the EMS, hard target zones neither entail a formal commitment for exchange rate intervention nor there is analog to the credit facilities of the EMS. The soft version of target zones differs from existing IMF surveillance. Whether measured in real or nominal terms, bilateral or effective terms, and the short-run variability of exchange rates over the period of managed floating has been high-indeed, significantly higher than during the previous Bretton Woods system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet